And they all lived happily ever after? A critical analysis of the Disney princess phenomenon - Muir, Robyn (2020)
Disney princess films and marketing have captured the hearts of children and adults all over the world. However, they may also contain gendered messages that reinforce traditional societal expectations of men and women. This thesis examines the Disney princesses, a worldwide commercial and cultural phenomenon that made $1.686bn just in 2018 (The Licensing Letter 2019). The Disney princesses are 16 royal women featured within animated Disney and Pixar films that are loved by young girls across the globe. This research will explore the Disney princess phenomenon, aiming to answer the following research question: ‘How is femininity depicted within the Disney princess phenomenon?’ through facet methodology.